2014
DOI: 10.4097/kjae.2014.67.5.299
|View full text |Cite
|
Sign up to set email alerts
|

Opioid induced hyperalgesia in anesthetic settings

Abstract: Pain is difficult to investigate and difficult to treat, in part, because of problems in quantification and assessment. The use of opioids, combined with classic anesthetics to maintain hemodynamic stability by controlling responses to intraoperative painful events has gained significant popularity in the anesthetic field. However, several side effects profiles concerning perioperative use of opioid have been published. Over the past two decades, many concerns have arisen with respect to opioid-induced hyperal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 45 publications
(55 reference statements)
2
20
0
Order By: Relevance
“…The addition of [Sar 9 , Met(O 2 ) 11 ] to the substance P-conjugated to saporin makes the agent more stable and potent than when substance P alone is bound to saporin. The dose and pretreatment interval was based on the studies of Wiley et al (2007) and Choi et al (2012), who observed no loss of intrinsic lumbar dorsal horn neurons expressing the neurokinin 1 (NK1) receptor in deeper laminae and prominent loss of NK1 receptor in laminae I, and studies by others (Khasabov et al, 2002;Vierck et al, 2003;Wiley et al, 2007;Choi et al, 2012;Weisshaar and Winkelstein, 2014;Kras et al, 2015;Araldi et al, 2016aAraldi et al, , 2017bAraldi et al, , 2018.…”
Section: Intrathecal Administration Of Saporinsmentioning
confidence: 99%
“…The addition of [Sar 9 , Met(O 2 ) 11 ] to the substance P-conjugated to saporin makes the agent more stable and potent than when substance P alone is bound to saporin. The dose and pretreatment interval was based on the studies of Wiley et al (2007) and Choi et al (2012), who observed no loss of intrinsic lumbar dorsal horn neurons expressing the neurokinin 1 (NK1) receptor in deeper laminae and prominent loss of NK1 receptor in laminae I, and studies by others (Khasabov et al, 2002;Vierck et al, 2003;Wiley et al, 2007;Choi et al, 2012;Weisshaar and Winkelstein, 2014;Kras et al, 2015;Araldi et al, 2016aAraldi et al, , 2017bAraldi et al, , 2018.…”
Section: Intrathecal Administration Of Saporinsmentioning
confidence: 99%
“…Although the underlying mechanism of OIH is not yet completely understood[1, 3, 4, 10], previous reports from our groups have shown that CaMKIIα, which is highly expressed in the CeLC and superficial spinal dorsal horn, plays an important role in modulation of OIH[11, 12]. Either spinal or CeLC CaMKIIα inhibition can attenuate OIH [11, 12].…”
Section: Introductionmentioning
confidence: 99%
“…OIH is related to high opioid dosage, long duration of opioid use, and abrupt discontinuation of opioids after surgery. Therefore, many mechanism- based combinations of other adjuvant drugs have been used to attenuate sensitization of the central pronociceptive process and reduce the unpleasant hyperalgesic response [ 1 ].…”
Section: Introductionmentioning
confidence: 99%